The Weakening or Enhancing of $N$-$H… O$ Intermolecular Hydrogen Bond in Different Solvents Revealed by Density Functional Calculations (Journal of Atomic and Molecular Sciences, 2022)
Time-dependent density functional theory (TDDFT) method has been performedto investigate the properties of $N_1$-$H_1… O_1$ hydrogen bond of $N$-methylaniline-DMSO complex (complex I) and $N$-methylaniline-acetone complex (complex II) in theexcited state. The infrared spectra are in good agreement with the experiment data.The analysis of the bond length and AIM (atoms in molecules) demonstrated that the $N_1$-$H_1… O_1$ hydrogen bond is weakening from DMSO to acetone in the ground state.That is to say, the intermolecular hydrogen bond $N_1$-$H_1 … O_1$ between $N$-methylanilineand solvent molecular is stronger with the polarity of solvent stronger. Upon photoexcitation,the analysis of AIM implies that the intermolecular complex II is enhanced.Interestingly, the hydrogen bond $N_1$-$H_1… O_1$ of complex I is weakened. The analysisof molecular orbital also support the results that the intermolecular hydrogen bond $N_1$-$H_1 … O_1$ of complex I is weakened whereas it of complex II is enhanced.
Keywords: hydrogen bond; electrostatic potential; AIM; N-methylaniline; DFT.